The effects of living wage laws on low-wage workers and low-income families: What do we know now? - David Neumark; Matthew Thompson; Leslie Koyle (IZA Journal of Labor Policy, 2012)
We provide updated evidence on the effects of living wage laws in U.S. cities, relative to the earlier research covering only the first six or seven years of existence of these laws. There are some challenges to updating the evidence, as the CPS data on which it relies changed geographic coding systems in the mid-2000s. The updated evidence is broadly consistent with the conclusions reached by prior research, including a recent review of that earlier evidence. Living wage laws reduce employment among the least-skilled workers they are intended to help. But they also increase wages for many of them. This implies that living wage laws generate both winners and losers among those affected by them. For broader living wage laws that cover recipients of business or financial assistance from cities, the net effects point to modest reductions in urban poverty.
Keywords: J23; J38; 330; living wages; wages; employment; poverty; Mindestlohn; Wirkungsanalyse; Niedriglohn; Niedrigeinkommen; Beschäftigungseffekt; Armut; USA